Vector Field Driven Design for Lightweight Signal Processing and Control Schemes for Autonomous Robotic Navigation. (26th May 2009) - Mathai Mathai, Nebu John Nebu John; Zourntos Zourntos, Takis Takis; Kundur Kundur, Deepa Deepa
Abstract : We address the problem of realizing lightweight signal processing and control architectures for agents in multirobot systems. Motivated by the promising results of neuromorphic engineering which suggest the efficacy of analog as an implementation substrate for computation, we present the design of an analog-amenable signal processing scheme. We use control and dynamical systems theory both as a description language and as a synthesis toolset to rigorously develop our computational machinery; these mechanisms are mated with structural insights from behavior-based robotics to compose overall algorithmic architectures. Our perspective is that robotic behaviors consist of actions taken by an agent to cause its sensory perception of the environment to evolve in a desired manner. To provide an intuitive aid for designing these behavioral primitives we present a novel visual tool, inspired vector field design, that helps the designer to exploit the dynamics of the environment. We present simulation results and animation videos to demonstrate the signal processing and control architecture in action.